2022
DOI: 10.1038/s41523-022-00394-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age and nodal status on variations in oncotype DX testing and adjuvant treatment

Abstract: Oncotype DX (ODX) recurrence score (RS) is a validated tool to guide the use of adjuvant chemotherapy (AC) in hormone receptor+/HER2- breast cancer. In this analysis, we examine (1) characteristics associated with ODX testing and (2) the association between ODX RS and receipt of AC across age and nodal status. Women with HR+/HER2–, early-stage (T1-2, N0-1) breast cancers from 2010–2017 in the National Cancer Database were included. 530,125 met inclusion and 255,971 received ODX testing. Older women were less l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Furthermore, in a study with 418 older patients above 70, Noordhoek et al found that patients with high clinical risk based on the St. Gallen risk classification, but classified as ultra-low risk by the 70-gene signature, had excellent prognosis (37). Regarding RS, Iles et al showed a decline in its usage with increasing age and a higher prevalence of low-risk classifications in patients above 70 years old (38). ER+/LN-/HER2-patients derive low or no benefit from chemotherapy if a tumour is classified as RS low (32) and in line with this, Barni et al found a 38% relative reduction of chemotherapy usage in 230 older patients on the basis of RS (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a study with 418 older patients above 70, Noordhoek et al found that patients with high clinical risk based on the St. Gallen risk classification, but classified as ultra-low risk by the 70-gene signature, had excellent prognosis (37). Regarding RS, Iles et al showed a decline in its usage with increasing age and a higher prevalence of low-risk classifications in patients above 70 years old (38). ER+/LN-/HER2-patients derive low or no benefit from chemotherapy if a tumour is classified as RS low (32) and in line with this, Barni et al found a 38% relative reduction of chemotherapy usage in 230 older patients on the basis of RS (39).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding RS, Iles et al . showed a decline in its usage with increasing age and a higher prevalence of low-risk classifications in patients above 70 years old(38). ER+/LN-/HER2-patients derive low or no benefit from chemotherapy if a tumour is classified as RS low(32) and in line with this, Barni et al .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we feel that policy and guidance restraints have been a barrier to more effective diagnostic testing and treatment individualization among older patients with BC, a finding supported in the literature. 41,42 Our QI exercise is framed within a PDSA cycle approach, 19 with a follow-up planned in 2 years to analyze the clinical pattern of RS utilization and related chemotherapy prescription. The effort will also include a reassessment of the time from surgery to initiation of chemotherapy on the basis of the new criteria to understand the impact of reflex testing patterns on treatment delays of >8 weeks, most likely to be detrimental on the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that RS correlates with recurrence rates and adjuvant treatment response [5,9,[12][13][14]. The National Comprehensive Cancer Network (NCCN) and the American Society of Clinical Oncology (ASCO) both recommended the use of Oncotype Dx RS testing in patients with ER + /HER2 − breast cancers [15,16]. Moreover, the Guidelines Development Group of the European Commission Initiative on Breast Cancer recently prioritized a clinical question on the use of multigene test to guide the use of adjuvant chemotherapy in ER + , HER2 − , and lymph node-negative or up to 3 lymph node-positive invasive breast cancer [17].…”
Section: Introductionmentioning
confidence: 99%